2014
DOI: 10.1002/hec.3070
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Taxing Sugar‐sweetened Beverages Across Different Income Groups

Abstract: Taxes on sugar sweetened beverages (SSBs) -so called 'soda taxes' are currently receiving considerable attention as a potentially very effective policy intervention in the fight against rising obesity rates all-over the world. By increasing the price of sugar sweetened beverages, taxes promise to reduce sugar intake and subsequently bodyweight of individuals. However, there are concerns that such taxes are regressive, i.e. burden lower income groups more. This paper explores this issue by estimating the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(166 citation statements)
references
References 38 publications
13
147
5
1
Order By: Relevance
“…Furthermore, research has shown that even a minimal reduction in BMI has the potential power to change an individual's weight status from obesity to overweight and from overweight to normal weight [64,65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, research has shown that even a minimal reduction in BMI has the potential power to change an individual's weight status from obesity to overweight and from overweight to normal weight [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that the burden of this SSB tax would be higher among low-income households ($17.87 AUD, 0.21% of annual income) compared with high-income households ($15.17 AUD, 0.07% of annual income) [64]. Lin et al reported similar results for the USA: a heavier tax burden for low-income households ($19.97 USD, 1.0% of food expenditures) compared with high-income households ($18.84 USD, 0.6% of food expenditure) [49].…”
Section: In High-income Countriesmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous simulations using econometrically estimated price elasticity of SSB demand showed that expected calorie reductions from a 20% targeted tax on SSBs, assumed to fully pass on to retail prices, may significantly reduce weight, obesity prevalence, and diabetes incidence [28,31,32]. However, quasi-experimental studies show that current soda taxes do not influence overall calorie intake and are ineffective in reducing population weight, but they may have larger effects in specific high-risk populations [33e36].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated change in BMI Haby MM et al (34) and Sharma A et al (33) Mean, SE Lognormal By age and sex…”
mentioning
confidence: 99%